2008
DOI: 10.1177/073953290802900302
|View full text |Cite
|
Sign up to set email alerts
|

How Newspaper Readership Affects Political Participation

Abstract: This analysis reveals that a decrease in newspaper readership among 17- to 24- year olds is associated with their decreasing political participation but not with a decrease in their political knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The number of observations reflects 4 months of data for 79 sites, i.e., 4 * 79 = 316. Lee and Wei (2008) find that a decrease in newspaper readership among 17-to 24-year olds is associated with a decline in political participation.…”
Section: Empirical Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The number of observations reflects 4 months of data for 79 sites, i.e., 4 * 79 = 316. Lee and Wei (2008) find that a decrease in newspaper readership among 17-to 24-year olds is associated with a decline in political participation.…”
Section: Empirical Analysismentioning
confidence: 93%
“…Indeed, studies have shown that the diffusion of news media is associated with positive spillovers on civic awareness and engagement (Mondak, 1995a,b;Lee and Wei, 2008;Oberholzer-Gee and Waldfogel, 2009;Gentzkow et al, 2009). Though the Internet facilitates the spread of information, it is not clear how or whether news organizations should charge for their content and how this might affect consumption of the news.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has detected significant differences in the effects of electronic versus print media on political knowledge. Newspaper readers, for instance, tend to obtain and retain more political information (Chaffee & Frank, 1996; Chaffee, Ward, & Tipton, 1970; Chaffee, Zhao, & Leshner, 1994; Clarke & Fredin, 1978; Kessel, 1980; Klapper, 1960; Lee & Wei, 2008) and can better discriminate among issues compared to television viewers (Choi & Becker, 1987; Wagner, 1983). As Viswanath and Finnegan (1996) argued, television's emphasis on entertainment rather than learning makes it a poor information provider.…”
Section: Discussionmentioning
confidence: 99%
“…This finding seems to counter Norris's (1996) contention that exposure to hard news in the newspaper and radio have a strong positive correlation with political interest and consequently, political participation as well as trust in public figures and institutions. Lee and Wei (2008) found that a decrease in newspaper reading among baby boomers and generation Y is associated with their decreasing political participation. They note that there has been a decline in political participation through signing petitions, attending rallies to voting in America.…”
Section: Research Question Onementioning
confidence: 99%
“…They note that there has been a decline in political participation through signing petitions, attending rallies to voting in America. Young American's political involvement has declined the most precipitously (Lee & Wei, 2008). Ali and Fatima (2016) who found that newspaper reading among Pakistani youth, which together with the Internet are the most preferred medium of information seeking, are strongly and positively correlated with their political awareness, knowledge, interest, and participation, which explains the healthy democratic system in Pakistan.…”
Section: Research Question Onementioning
confidence: 99%